Against strong pluralism - Noonan, Harold W. (Springer, 2015)
Strong pluralists hold that not even permanent material coincidence is enough for identity. Strong pluralism entails the possibility of purely material objects -- even if not coincident -- alike in all general respects, categorial and dispositional, relational and non-relational, past, present and future, at the microphysical level, but differing in some general modal, counterfactual or dispositional repscts at the macrophysical level. It is objectionable because it thus deprives us of the explanatory resources to explain why evident absurdities are absurd. A second objection is to the suggestion that cases involving artefacts can illustrate strong pluralism. This offends against the principle that gien a complex intrinsic microphysical property instantiated in some regiion, the number of material things possessing it in that region cannot depend on the existence and nature of intentional activity taking place outside it.